Toughening and brittle-tough transition in polyamide 12-organoclay/maleated styrene-ethylene-co-butylene-styrene nanocomposites - González, Imanol; Zabaleta, Asier; Eguiazábal, José Ignacio (Polymer engineering and science, 2013)
Tough nanocomposites based on polyamide 12 (PA12) can be obtained by the addition of a maleated rubber to a highly dispersed PA12‐clay nanocomposite by melt processing. The nanostructure behavior was evaluated by X‐ray diffraction and transmission electron microscopy. The results showed that the organoclay was highly dispersed and mostly located in the PA12 matrix due to the larger affinity between the polyamide and the clay, but some of the organoclay was also present in the polymer/polymer interface. The presence of organoclay slightly increased the dispersed particle size, indicating decreased compatibilization. This was attributed to a partial shielding of maleic anhydride compatibilizer by surfactant. The addition of the elastomer considerably improved the toughness of the PA12‐based nanocomposites, maintaining its stiffness; i.e., the nanocomposites with 25% rubber content showed an increase of 25‐fold of notched impact strength of the PA12 matrix, meanwhile ductility and stiffness remained constant. This allowed us to obtain toughened PA12 PNs throughout a large range of strain rate and a modulus similar to that of the unmodified PA12. The position of the brittle/tough transition in terms of rubber content, determined by the standard notched Izod test (25% mSEBS) is basically the same as that determined by the essential work of fracture procedure. POLYM. ENG. SCI., 2013. © 2012 Society of Plastics Engineers